The Shofar and Trumpet in Byzantine Art - Demi̇r, Hatice (Istanbul University Press, 2021)
The subject of this study involves the shofar and trumpet, instruments usedboth in liturgical and secular ceremonies, and their reflections in religiousart. The article addresses these instruments under certain sub-headings. Theintroduction attempts to explain the emergence of the shofar as an instrument.The trumpet, being frequently mentioned in the Bible, is also included to thecontext of the study. References to trumpets and shofars were compared interms of how they were mentioned both in paganism and in the Bible. Theother sub-headings first examine the etymological and then iconographicpast of the shofar and trumpet. While evaluating the origin of the shofar, theiconographic facts were identified as having important points regarding theetymological derivation of shofar. Chapter 20 in the Bible’s Book of Genesisdeals with how God tests Abraham and sends a ram to replace Isaac upon thesacrificial altar and how the ram’s horn has an important place in identifyingthe shofar’s etymological, material, and iconographic past. This event, known asthe Akedah, has an important place in the Hebrew tradition. For these reasons, the places and usages of shofar and trumpet were classified according to their references given in the Bible. Anotherimportant sub-heading of the study explains the depictions of the shofar and trumpet in religious art that werechosen as examples. The conclusion heading provides a general evaluation using the given examples.

Bu çalışmanın konusunu hem liturji hem de seküler hayattaki törenlerde kullanılan bir çalgı olan şofar ve kullanıldığı yerlerin dinî tasvir sanatına yansımaları oluşturmuştur. Çalışma, birkaç alt başlık altında ele alınmıştır. Giriş bölümünde şofarın bir çalgı olarak nasıl ortaya çıktığı açıklanmıştır. Bu bağlamda, Kitab-ı Mukaddes’te adı sıkça geçen trompet de çalışma kapsamına alınmıştır. Trompet ve şofarın gerek çok tanrılı dönem ve gerekse Kitab-ı Mukaddes’te kullanıldığı yerler karşılaştırılmıştır. Diğer alt başlıklarda; şofarın etimolojisi ve ikonografik geçmişi irdelenmiştir. Etimolojik kökeni değerlendirilirken, şofar adının kökeninde, ikonografik etkenin de önemli olduğu noktası tespit edilmiştir. Kitab-ı Mukaddes Yaratılış episodu 22. Bab’da İbrahim’in Denenmesi olayında oğlu İshak’ı kurban etme ile sınanan İbrahim’e bir koç gönderilmiş ve bu koçun boynuzu şofarın hem etimolojik hem malzeme ve hem de ikonografik geçmişi konusunda önemli olmuştur. Akedah olarak bilinen bu olayın İbrani geleneklerinde önemli bir yeri vardır. Bu nedenle, Kitab-ı Mukaddes’te şofar ve trompetin kullanım yerleri amaçlarına göre sınıflandırılmıştır. Çalışma konusunun önemli bir diğer alt başlığında, şofarın dinî tasvir sanatındaki yeri örnekler ile açıklanmıştır. Sonuç bölümünde ise şofarın dinî tasvirlerdeki seçimleri ile ilgili olarak genel bir değerlendirme yapılmıştır.
Keywords: Şofar; Trompet; Bizans; Kitab-ı Mukaddes; Dinî Tasvir; trumpet; byzantium; shofar; History of the arts; religious depiction shofar; religious depiction; NX440-632; Shofar; trumpet; Byzantium; Bible; religious depiction; bible